Use one of the #tan# half-angle identity:
#tan(theta/2)=+-sqrt((1-costheta)/(1+costheta))#
#color(white)(tan(theta/2))=(1-costheta)/sintheta#
#color(white)(tan(theta/2))=(sintheta)/(costheta+1)#
I will use the third one, because it works out well in this case. First, factor out the #tan(t/2)#, then use the identity, and lastly rewrite #cost# as #1/(1/cost)#:
#LHS=tan (t/2) (cos^2t) - tan(t/2)#
#color(white)(LHS)=tan(t/2)(cos^2t-1)#
#color(white)(LHS)=tan(t/2)(cost-1)(cost+1)#
#color(white)(LHS)=sint/(cost+1)*(cost-1)(cost+1)#
#color(white)(LHS)=sint/color(red)cancelcolor(black)((cost+1))*(cost-1)color(red)cancelcolor(black)((cost+1))#
#color(white)(LHS)=sint*(cost-1)#
#color(white)(LHS)=sintcost-sint#
#color(white)(LHS)=sint*1/(1/cost)-sint#
#color(white)(LHS)=sint*1/(sect)-sint#
#color(white)(LHS)=sint/(sect)-sint#
#color(white)(LHS)=RHS#
That's the proof. Hope this helped!